Movimientos de mujeres indígenas en Latinoamérica: género y etnicidad en el Perú, México y Bolivia de Stéphanie Rousseau & Anahi Morales Hudon (2018) & Violence against women in legally plural settings. Experiences and lessons from the Andes by Anna Barrera (2016) - Vergara Rodríguez, Roxana (Critical Reviews on Latin American Research - CROLAR, 2021)
.